Предмет: Алгебра,
автор: t123654
разложить на множители 125-a³= решить уравнение х(х+3) (х-1)=х²(х+2)
anastasiyaalek13:
x^3+6x^2-x-6=(x^3+6x^2)-(x+6)=x^2(x+6)-(x+6)=(x+6)(x^2-1). (x^2-1)=(x-1)(x+1). (x+6)(x-1)(x+1)=0, x1=-6, x2=1, x3=-1. Ответ: x1=-6, x2=1, x3=-1.
Ответы
Автор ответа:
2
,,,,,,,,,,,,,,,,,,,,,,,,,,,
Приложения:
Похожие вопросы
Предмет: Математика,
автор: dutovaarina592
Предмет: Другие предметы,
автор: alievnidzat200
Предмет: Қазақ тiлi,
автор: ajnazajlaubaj
Предмет: Алгебра,
автор: mishka113